Glycaemic stability of a cyclist with Type 1 diabetes: 4011 km in 20 days on a ketogenic diet. Issue 11 (4th July 2019) - Nolan, J.; Rush, A.; Kaye, J.
Abstract: Background: Maintaining glycaemic control during exercise presents a significant challenge for people living with Type 1 diabetes. Significant glycaemic variability has been observed in athletes with Type 1 diabetes in competitive contexts. While very‐low‐carbohydrate ketogenic diets have been shown to minimize glycaemic excursions, no published data have examined if this translates to exercise. Case report: We report the case of a 37‐year‐old man with Type 1 diabetes who successfully undertook a 4011 km cycle across Australia over 20 consecutive days whilst consuming a very‐low‐carbohydrate ketogenic diet. Continuous glucose monitoring data capture was 98.4% for the ride duration and showed remarkable glycaemic stability, with a standard deviation of 2.1 mmol/l (average interstitial glucose 6.1 mmol/l) and 80.4% of time spent within a range of 3.9–10 mmol/l. Interstitial glucose was <3 mmol/l for 2.1% of this time, with only a single episode of symptomatic hypoglycaemia prompting brief interruption of exercise for carbohydrate administration. Conclusion: This case demonstrates the viability of a very‐low‐carbohydrate ketogenic diet in an individual with Type 1 diabetes undertaking exercise. While the effect of a very‐low‐carbohydrate ketogenic diet is yet to be examined more broadly in athletes with Type 1 diabetes, the glycaemic stability observed suggests that fat adaptation may attenuate glycaemic swings and reduce reliance on carbohydrate consumption during exercise for maintaining euglycaemia. What's new?: The benefits of exercise in Type 1 diabetes are well understood. Uptake is suboptimal despite this, partly as a result of glycaemic instability. Reduced glycaemic variability has been observed in individuals consuming ketogenic diets. Remarkable glycaemic stability was observed in a person with Type 1 diabetes exercising at moderate to high intensities over 20 consecutive days while consuming a ketogenic diet. A ketogenic diet is a viable dietary strategy for individuals with Type 1 diabetes who exercise. It may attenuate glycaemic fluctuations and reduce the carbohydrate required to maintain euglycaemia during exercise. Lower average glucose may increase the risk of hypoglycaemia and warrants collaboration with healthcare professionals.